Windows PowerShellTM 3.0 step by step\n - Wilson, Ed (O'Reilly Media, Inc. CaliforniaUS, 2013)
Focuses on Windows PowerShell 3.0 - a management and automation tool which enables standardisation and automation of the installation and configuration of dot-net networking components; and automation of the day-to-day management of dot-net networks.